Temples, tithes, and taxes: the temple and the economic life of ancient Israel - Stevens, Marty E. (Hendrickson, 2006)
Introductory matters -- Temple construction -- Temple personnel -- Temple income -- Temple expenses -- Temple as "bank" -- Concluding matters